Growing up with jazz : twenty-four musicians talk about their lives and careers - Stokes, W. Royal (New York : Oxford University Press, 2005)
Focusing on how these figures became jazz musicians, this volume discusses the two most prominent US jazz musicians: the influential bop drummer Art Blakely and the famous jazz pianist and personality Dr Billy Taylor.
Introduction -- Keepers of the flame -- Modernists -- Visionaries and eclectics.
Includes index.
Print version record.
eBooks on EBSCOhost
Keywords: Jazz musicians -- Interviews; Musiciens de jazz -- Entretiens; MUSIC -- Genres & Styles -- Jazz; Jazz musicians; Interviews